The Indonesian Genocide of 1965 Causes, Dynamics and Legacies (Palgrave Studies in the History of Genocide, 2018)
This collection of essays by Indonesian and foreign contributors offers new and highly original analyses of the mass violence in Indonesia which began in 1965 and its aftermath. Fifty years on from one the largest genocides of the twentieth century, they probe the causes, dynamics and legacies of this violence through the use of a wide range of sources and different scholarly lenses. Chapter 12 of this book is available open access under a CC BY 4.0 license at link.springer.com.